Peran Guru PAI-BP dalam Menerapkan Kurikulum Merdeka di SMPN 3 Panyabungan - Saddam Husein; Syamsiah Depalina Siregar; Nelmi Hayati (PT. Willy Print Art, 2024)
This research is motivated by the emergence of the latest curriculum, namely the independent curriculum, where SMPN 3 Panyabungan has implemented the independent curriculum. Of course, implementing independent curriculum learning cannot be separated from the role of a teacher. The role of the teacher here is very important considering that this curriculum is still new and teachers need to study and study this independent curriculum in more depth so that the learning process can run smoothly and learning objectives can be achieved. The problem that arises is the role and obstacles of PAI-BP teachers in implementing independent curriculum learning at SMPN 3 Panyabungan. This type of research uses descriptive qualitative research. The data sources for this research consist of two, namely primary data: PAI-BP teachers, and secondary data from school principals, students and other supporting documents. Data collection was obtained through observation, interviews and documentation. The data validity technique in this research uses triangulation of sources and techniques. Data were analyzed through data reduction, data presentation and drawing conclusions. The results of this research show that the role of PAI-BP teachers in implementing independent curriculum learning, starting from the role of PAI-BP teachers as educators and instructors, as community members, as leaders, as administrators and as learning managers, has been implemented quite well. However, there are several obstacles experienced by PAI-BP teachers in implementing independent curriculum learning so that it has not been implemented optimally, such as a lack of teacher proficiency in using IT, inadequate infrastructure in the form of media that can support the smooth learning process, and students who are unable to adapt the concepts. Independent curriculum learning, as well as limited teacher time in carrying out assessments considering that PAI-BP subjects only take 2 hours per week.